Spurious-free thickness-shear bulk acoustic resonators on lithium niobate using standard and broadband piston mode designs. (21st January 2022) - Wu, Ting; Wong, Yu-po; He, Yi-wen; Peng, Chuan; Bao, Jing-fu; Hashimoto, Ken-ya
Abstract: This paper describes the design and fabrication of spurious-free thickness-shear bulk acoustic resonators (TSBARs) using the lithium niobate (LN) plate. Previously, the authors conjected from the experiment on the TSBAR that cut-off edges with crystal LN x plane serve as ideal reflectors for the piston mode operation, and complete suppression is possible by adding the standard piston mode design to the other edges normal to the X -axis. Following this conjecture, the traditional piston mode structure is designed by the traditional two-dimensional finite element method, and the TSBAR is fabricated following the design. The experiment showed complete suppression of the transverse mode resonances, and the conjecture was verified.